Pengaruh Permainan Edukasi “Puzzlo Puzzle” Terhadap Peningkatan Kemampuan Motorik Halus dan Kognitif Anak Usia 4-5 Tahun - Lavenia Elizya STT; Krisni Subandijah; Mergy Gayatri (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
. Stimulation plays a crucial role in maximizing the growth and development of children by targeting their specific age-related cognitive and fine motor skills. This study aims to investigate the effectiveness of the educational toy "Puzzlo Puzzle" in improving the fine motor and cognitive abilities of children aged 4-5 years. The research design employed a pre-experimental approach with a one-group pretest-posttest design. A total of 36 participants were included, and primary data was collected through questionnaires assessing fine motor and cognitive development. The data were analyzed using frequency distribution tables and the paired t-test. The results indicated a significant relationship between the utilization of the puzzlo puzzle educational game and the improvement of both fine motor skills (p < 0.05) and cognitive abilities (p < 0.05) in children aged 4-5 years. Therefore, parents and educators should maximize the use of the "Puzzlo Puzzle" educational game in the child's educational journey.